The effects of Atlantic salmon aquaculture on decapod crustaceans and fishes in the Quoddy region of the Bay of Fundy - Hulmes, Lloyd, 1991- (2017)
The Food and Agriculture Organization (FAO) reported in 2016 that aquaculture production had doubled since 2001, indicating exponential growth in the industry that has a global value of more than $200 billion CAD. In New Brunswick, Canada, there is concern that the activities of the aquaculture industry are having a detrimental effect on benthic communities, with an emphasis on the commercially-important American lobster. The aim of this thesis was to monitor the impacts of the aquaculture industry on decapod crustaceans and fishes in the Quoddy Region, New Brunswick. Cobble-filled collectors were deployed at paired sites near and away from aquaculture cages at shallow subtidal locations in three Bay Management Areas (BMAs) in the Quoddy region in 2015 and 2016, where near sites were approximately 200 m in distance from aquaculture operations, compared to 1200 m for the away sites. No significant effect of proximity to aquaculture on fish and decapod communities in terms of individual abundance, species richness and species evenness was found; while a significant interaction between year and BMA was observed in a PERMANOVA of decapod and fish data. Abundance of lobster was not significantly different between treatments, apart for one site pair. At present, there is no evidence to suggest that there is an effect of aquaculture on fish and decapod crustaceans on cobble habitat ~200 m away from aquaculture pens. Due to the three year production cycle of Atlantic salmon in the Quoddy region, another year of data is required to confirm this finding. Keywords: Decapods, fish, Quoddy region, aquaculture, individual abundance, species richness, New Brunswick.